ANALYSIS OF A MICROCYCLE IN PREPARATION FOR THE ATHLETIC DISCIPLINE 1500 m. WITH MARIJA STOJANOVSKA - Simeonov, Aleksandar; Marija Stojanovska (Faculty of Physical Education, Sport and Health, Skopje, 2022)
When planning training programs, repetitive training periods are used, in the form of cycles (weekly, monthly, annual). This is done in order for the (coach) to be able to prepare the idea for the training program more clearly, but also in order to adapt the athlete's biorhythm to the planned system of competitions. When creating any cycle in athletics, the components for: intensity, volume, weekly training frequency are always taken into account, as well as rest during and after the training. A key point in creating training cycles is dosing the training components. In this paper, a microcycle is presented in the phase of specific preparation, by the athlete Marija Stojanovska.
Keywords: analysis, training, phases, dosing, microcycle...